Spatiotemporal organization of standing postprandial contractions in the distal ileum of the anesthetized pig. Issue 11 (24th September 2014) - Janssen, P. W. M.; Lentle, R. G.; Chambers, P.; Reynolds, G. W.; De Loubens, C.; Hulls, C. M.
Abstract Background Spatiotemporal (ST) mapping has mainly been applied to ex vivo preparations of the gut. We report the results of ST mapping of the spontaneous and remifentanil‐induced motility of circular and longitudinal muscles of the distal ileum in the postprandial anaesthetized pig. Methods Spatiotemporal maps of strain rate were derived from image sequences of an exteriorized loop of ileum on a superfusion tray at laparotomy. Parameters were obtained by direct measurement from these maps, and by auto‐ and cross‐correlation of map segments. Key Results Localized domains of standing longitudinal and circular activity that alternated between neighboring domains occurred spontaneously and both were promptly extinguished following intraluminal dosage with lidocaine. Longitudinal or circular contractions within a domain typically occurred at times that would coincide with every second or third cycle of the slow wave but propagated within the domain at a rate consistent with that reported within spike patches. Shortly after intravenous administration of remifentanil, longitudinal and circular contractions at the reported slow wave frequency propagated over longer distances at a high speed before slowing to a rate similar to that reported for slow waves. Conclusions & Inferences ST mapping based on cross‐correlation is a robust tool for the analysis of intestinal movement and minimizing movement artefacts. We propose that the ST pattern of standing longitudinal and circular contractions arises from variation in the refractory period of smooth muscle, and hence, in its response to successive slow waves with neural stimuli influencing the former and having a mainly permissive role.